한국형 마음챙김 명상기반 스트레스 완화 프로그램(K-MBSR)이 유방암 환자의 심리적 증상, 수면 및 삶의 질에 미치는 효과 - 박경(Kyung Park); 전진수(Jin-Soo Jun); 정선용(Sun Young Jung) (Seuteureseu yeon-gu (Online), 2013)
본 연구에서는 유방암 환자들에게 K-MBSR의 효과를 검증하였다. 연구기간은 2월말에서 8월 9일까지이며, 실험집단2집단 15명(1차 9명, 2차 6명), 통제집단 1집단(6명)으로 구성되었다. K-MBSR을 마친 실험 집단 가운데 추후검증에참여한 환자는 6명이다. 실험집단 2집단에게 일주일 4시간씩 6주간의 K-MBSR이 실시되었으며, 통제집단은 대기집단으로 무처치 집단으로 사전, 사후에 측정도구를 실시하였다. 프로그램 사전 사후에 실시한 측정도구는 RRS, PSQI, EROTC-BR23, SCL-90-R, FFMQ, K-CCQ, K-TPGI이며 혈압도 함께 측정하였고, 타액검사를 실시하였다. 우선 실험집단및 통제집단의 연구 참여자들의 동질성 가정에 대한 검토를 한 결과, 실험집단 15명과 통제집단과는 사전점수 비교에서 유의하게 나타난 척도가 없어 동질성 가정이 확인되었다. 프로그램 6회기를 모두 마친 실험집단의 K-MBSR 효과검증 결과는 MBSR 프로그램에 의한 유방암 환자들의 반추양식과 수면 질 그리고 삶의 질에서의 신체증상 및우울과 대인관계 민감성과 적대감이 감소되었다. 실험 집단 가운데 추후연구에 참여한 실험집단 6명과 통제집단5명의 사전, 사후의 비교는 명수의 제한 때문에 일반화하기에는 한계가 있으나, 실험집단의 경우, 사전-사후간 우울은 유의하게 감소하였다. 이는 유방암 환자들이 흔히 보고하고 호소하는 우울의 문제가 마음챙김 훈련에 통해 장기적이고 지속적으로 효과가 있다는 고무적인 결과이다. 본 연구의 결과 여러 심리적 신체적 변인에 긍정적인 효과를확인 할 수 있었다. 그러나 연구 대상자 수 및 기간의 제한 등으로 마음챙김의 장기적 효과에 대한 검증은 향후재검토 해야 할 과제 중 하나이다. 본 연구 결과를 토대로 향후 연구방향에 대해 논의하였다. This study investigated the effects of K-MBSR in Korean breast cancer patients. research period was from the end of Feb. to 9th of Aug. in 2012. 20 breast cancer patients were participated in this program. 5 were assigned in non-treatment control group and 15 were assigned in experiment group. And 6 of experimental group who engaged in first experiment were participated in follow-up study. K-MBSR was implemented to experimental group for 4 hours for every week during 6 weeks. The control group did not have any treatment. The test instruments for pre-post experiment were RRS, PSQI, EROTC-BR23, SCL-90-R, FFMQ, K-CCQ, K-TPGI, Blood Pressure, and Salivary Test in this program. As the results of hypothesis pre-tests for homogeneity between experimental and control group, all the null hypothesis were accepted. However, after the 6 times K-MBSR treatments, several null hypothesis were denied, and research hypothesis were accepted such as Ruminative Response, Sleep Quality, physical symptoms of Quality of Life, Depression Hostility, Interpersonal Sensitivity, and Anxiety. This means that experimental group patients experienced some reduction for the tested issues. Especially depression in pre-post of experiment group showed significant reduction. Especially depression in pre-post of experiment group was a significant reductions. Although the number of cases was small, these results implies that the K-MBSR can contribute reductions for the rumination, physical symptoms, Sleep Quality, and Quality of Life of the breast cancer patients in Korea. For the future research, large sample experiment is needed to make more confident result for K-MBSR. (Korean J Str Res 2013;21:249∼262) KCI Citation Count: 23